"We're Just Not Prepared for Eating Over Our Whole Life": A Mixed Methods Approach to Understanding Dietary Behaviors Among Longer Term Cancer Survivors. (June 2018) - Klassen, Ann Carroll; Smith, Katherine Clegg; Shuster, Michelle; Coa, Kisha I.; Caulfield, Laura E.; Helzlsouer, Kathy J.; Peairs, Kimberly S.; Shockney, Lillie D.; Stoney, Dara; Hannum, Susan
Background: In many countries, there are growing numbers of persons living with a prior diagnosis of cancer, due to the aging population and more successful strategies for treatment. There is also growing evidence of the importance of healthful diet and weight management for survivorship, yet many long-term cancer survivors are not successfully following recommendations.Methods: We explored this issue in a mixed methods study with 53 adult survivors of 3 cancers (breast, prostate, and non-Hodgkin's lymphoma), living in Maryland. Participants provided three 24-hour dietary recalls, and results were used to classify respondents on 2 metrics of healthful eating (the Healthy Eating Index 2010, and a 9-item index based on current dietary recommendations). Recalls were also used to guide in-depth qualitative discussions with participants regarding self-assessment of dietary behaviors, healthful eating, and diet's importance in cancer prevention and survivorship.Results: Survivors following a more healthful diet were more likely to be female, have greater socioeconomic resources, more years since diagnosis, normal weight, and no smoking history. Qualitative discussions revealed a more nuanced understanding of dietary strategies among healthful eaters, as well as the importance of household members in dietary decision making.Discussion: Most survivors had received little nutrition counseling as part of their cancer care, highlighting the importance of holistic, household-oriented nutrition education for maintaining health among long-term cancer survivors.